PENGARUH PENDAPAT IKHTIYĀRĀT IMAM AL-NAWAWῙ TERHADAP PENGEMBANGAN FIKIH SYĀFIʻIYYAH - Imran, Helmi; Abdul Kadir, Muntasir; Abdullah Lawang, Karimuddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the influence of Imam al-Nawawī's ikhtiyārāt (personal scholarly preferences) on the development of Shāfiʻī jurisprudence, particularly in altering the landscape of Shāfiʻī school thought, enriching the scholarly tradition, affirming the school’s opinions, and serving as a basis for legal fatwas. The research employed a qualitative method with a library research approach, involving an analysis of the book Rauḍat al-Ṭālibīn and other Shāfiʻī literature sources. Data were collected through document review and analyzed descriptively and analytically. The results indicate that al-Nawawī's ikhtiyārāt have reshaped the thought patterns of the Shāfiʻī school, establishing themselves as a primary reference in resolving disputed issues (khilafiyah). Furthermore, al-Nawawī’s innovations have enriched the intellectual heritage of the school and strengthened the affirmation of its opinions. These ikhtiyārāt have also become a crucial foundation in the issuance of legal fatwas. The implications of this research underscore al-Nawawī’s role as one of the leading scholars of the Shāfiʻī school, whose innovative thoughts and perspectives have significantly contributed to the development of Islamic jurisprudence.